2008
DOI: 10.1073/pnas.0809577105
|View full text |Cite
|
Sign up to set email alerts
|

Light-arousal and circadian photoreception circuits intersect at the large PDF cells of the Drosophila brain

Abstract: The neural circuits that regulate sleep and arousal as well as their integration with circadian circuits remain unclear, especially in Drosophila. This issue intersects with that of photoreception, because light is both an arousal signal in diurnal animals and an entraining signal for the circadian clock. To identify neurons and circuits relevant to light-mediated arousal as well as circadian phase-shifting, we developed genetic techniques that link behavior to single cell-type resolution within the Drosophila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
278
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 274 publications
(304 citation statements)
references
References 37 publications
17
278
0
Order By: Relevance
“…In addition, the l-LNvs promote light-mediated arousal, also mediated at least in part by PDF (23,29,35). Taken together with the fact that light has been shown to increase the firing rate of l-LNvs in a CRY-dependent manner (28), it is likely that lights on in the morning also potentiates the PDF-cAMP system.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, the l-LNvs promote light-mediated arousal, also mediated at least in part by PDF (23,29,35). Taken together with the fact that light has been shown to increase the firing rate of l-LNvs in a CRY-dependent manner (28), it is likely that lights on in the morning also potentiates the PDF-cAMP system.…”
Section: Discussionmentioning
confidence: 88%
“…Light enhances the firing rate of PDF neurons, and morning phase shifts appear to require the l-LNvs (28,29). Although TIM degradation is intimately connected with light-mediated phase shifts (24,(30)(31)(32), our recent study showed that PER degradation is also relevant (17).…”
Section: Relative Per Levelmentioning
confidence: 99%
“…Subsequent work on the LNv indicates that these neurons also mediate light-driven arousal behavior (9)(10)(11). The CRY-dependent rapid electrophysiological response to blue light recorded in the LNv suggests that the loss of CRY attenuates acute behavioral arousal responses to blue light, but not to wavelengths beyond its absorbance cutoff above 530 nm (1).…”
Section: Resultsmentioning
confidence: 99%
“…CRY is expressed in a small subset of central brain circadian, arousal, and photoreceptor neurons in D. melanogaster and other insects, including the large lateral ventral neuron (LNv; l-LNv) subset (1,2,7,8). The l-LNvs are light-activated arousal neurons (1,2,(9)(10)(11), whereas the small lateral ventral neurons (s-LNvs) are critical for circadian function (5,12). Previous results suggest that light activated arousal is likely attenuated in cry-null mutants.…”
mentioning
confidence: 99%
“…For insects, CRY is characterized as the primary photoreceptor for blue-light-activated circadian entrainment (15)(16)(17)(18)(19)(20)(21). CRY-expressing large LNvs (l-LNvs) also mediate acute behavioral arousal responses to blue-light-containing spectra (4)(5)(6)(7). Arousal and circadian functions are not strictly segregated between the LNv subsets because the small LNvs (s-LNvs) also contribute to arousal (5), and clock cycling is robustly altered in the l-LNv in response to light entrainment cues (22,23).…”
mentioning
confidence: 99%